Enhancing Financial Analysis Through Artificial Intelligence: A Comprehensive Review - Babatunde Adeyeri, Toluwani (Journal of Science & Technology, 2024)
Financial analysis serves as the cornerstone of decision-making processes within various domains including businesses, investment firms, and regulatory bodies. As the financial landscape continues to evolve, the integration of artificial intelligence (AI) technologies has emerged as a transformative force, reshaping traditional approaches to financial analysis. This comprehensive review delves into the multifaceted realm of AI in financial analysis, aiming to elucidate its applications, benefits, challenges, and future trajectories.The introduction outlines the foundational significance of financial analysis and delineates the pivotal role it plays in facilitating informed decisions across diverse sectors. With the advent of AI, particularly machine learning and deep learning techniques, there has been a paradigm shift in the methodologies employed for financial analysis, heralding a new era of data-driven decision-making.The subsequent section navigates through the expansive spectrum of applications wherein AI augments financial analysis capabilities. From predictive analytics for forecasting market trends to sentiment analysis for gauging investor sentiment, AI facilitates a myriad of functionalities that enhance the accuracy, efficiency, and timeliness of financial insights. Moreover, the integration of AI in algorithmic trading, fraud detection, risk management, and customer behavior analysis underscores its versatility and utility across various facets of finance.Highlighting the benefits of AI in financial analysis, the review delineates how AI-powered algorithms contribute to improved decision-making processes by harnessing vast amounts of data to generate actionable insights. The automation of repetitive tasks, coupled with real-time analytics capabilities, empowers financial professionals to make informed decisions swiftly, thereby enhancing operational efficiency and competitiveness.However, amidst the transformative potential of AI in financial analysis, several challenges and limitations warrant consideration. Issues pertaining to data quality, ethical concerns, regulatory compliance, and interpretability of AI algorithms pose formidable obstacles that necessitate careful navigation. Moreover, the risk of overreliance on AI systems and susceptibility to cybersecurity threats underscore the importance of establishing robust governance frameworks and ethical guidelines.Looking ahead, the review envisages a future brimming with opportunities for the continued evolution and integration of AI in financial analysis. Advancements in machine learning algorithms, coupled with the convergence of AI with emerging technologies such as blockchain, promise to unlock new frontiers in financial innovation. Moreover, the proliferation of AI applications in fintech and regtech domains heralds a seismic shift in how financial services are conceptualized, delivered, and regulated.Drawing upon case studies and success stories, the review provides empirical evidence of the tangible impact of AI implementation on financial performance and strategic decision-making. By synthesizing existing literature and empirical insights, this review contributes to the discourse surrounding AI in financial analysis, offering valuable insights for researchers, practitioners, and policymakers navigating the complex interplay between technology and finance.
Keywords: Artificial Intelligence; Machine Learning; Financial Analysis; Comprehensive Review; AI algorithms; Data